Earned Value Analysis Terhadap Biaya dan Waktu pada Proyek Pembangunan Gudang Produksi PP. Indopack Printing Nganjuk - Wiranegara, Dimas Gusti; Sarya, Gede; Triana, Masca Indra (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Earned Value Analysis is a technique of analyzing cost and time to obtain the performance achieved per time on a project, so that users are able to predict the cost and time required to complete the remaining project work. The prediction is calculated with the assumption that the performance of completing the rest of the project will be the same and constant as the performance obtained when the review was conducted. Thus, a system is needed to integrate cost and time information. The Earned Value concept is an analysis used in project management by integrating cost and time. The results show the value of Cost Variance (CV) week 16 during the review of Rp.1,995,516,896, Schedule Variance (SV) of Rp.-162,490,873 which shows there is no cost overrun in implementation but the schedule is not according to plan. While the Schedule Performance Index (SPI) value of 0.994 < 1 and Cost Performance Index (CPI) of 1.070 means that the project is delayed but still profitable. The results of the analysis of the costs required to complete the remaining project Estimate To Complate (ETC) at week 16 review with a value of Rp. 19,270,138,044. While the results of the analysis of the amount of time required to complete the Estimate To Schedule (ETS) project amounted to 126.76 with a rounding of 127 days.